2001
DOI: 10.1007/bf03017361
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled prostacyclin (PGI2) is an effective addition to the treatment of pulmonary hypertension and hypoxia in the operating room and intensive care unit

Abstract: Inhaled PGI2 can be useful in the treatment of patients with PHT and severe hypoxia. It can however be associated with systemic side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 25 publications
(29 reference statements)
0
33
0
3
Order By: Relevance
“…Prostacyclin and its analogues offer a good alternative to NO and there are several reports of the use of inhaled epoprostenol in the peri-operative setting. A study that included 35 patients with PH showed successful use of inhaled prostacyclin in the operating theatre and intensive care unit [72]. Iloprost has a longer half-life than prostacyclin and is less likely to cause rebound phenomena after discontinuation.…”
Section: Vasodilatorsmentioning
confidence: 99%
“…Prostacyclin and its analogues offer a good alternative to NO and there are several reports of the use of inhaled epoprostenol in the peri-operative setting. A study that included 35 patients with PH showed successful use of inhaled prostacyclin in the operating theatre and intensive care unit [72]. Iloprost has a longer half-life than prostacyclin and is less likely to cause rebound phenomena after discontinuation.…”
Section: Vasodilatorsmentioning
confidence: 99%
“…(9,33 ± 3,83 mmHg vs 17,09 ± 6,41 mmHg, P < 0,05). Le ratio de la pression artérielle pulmonaire moyenne sur la pression artérielle systémique a diminué pendant cette période (0,28 ± 0,08 vs 0,45 ± 0,17, P < 0,05).…”
unclassified
“…At the Montreal Heart Institute, iPGI 2 (Hache et al, 2001;Hache et al, 2003) and inhaled milrinone (Lamarche et al, 2005;Lamarche et al, 2007) are commonly administered to patients when PH and RV dysfunction occur before or after cardiac surgery. Oral sildenafil and iNO are also used in refractory cases in the ICU.…”
Section: Experience At the Montreal Heart Institutementioning
confidence: 99%